Elastic filler – products of reworked rubber by means of high-temperature shift crushing deformation - O. E. Bocharova; G. V. Nikolsky; I. A. Krasotkina; Yu. A. Naumova; V. A. Kozlov (Тонкие химические технологии, 2011)
In this article matters of investigation of basic physical, chemical and technical properties of a product of recycling rubber by means of high-temperature shift crushing deformation are considered.